Development of learning tools physics problem based learning model with phet assistance to improve the ability of critical thinking of junior high school students - N R Kapelle; B Jatmiko; M Munasir (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
The purpose of this research is to produce physic learning device regarding to thematerial of dynamic electricity by using problem based learning (PBL) assisted by PhET inguiding critical thinking skill of junior high school students. The objective details aregenerating the validity of learning tools developed through PBL model as well as teachingmaterials for students and student activity sheets, resulting the practice of instructional toolsdeveloped through PBL model, analyzing and describing the effectiveness of learning toolsdeveloped through PBL assisted by PhET reviewed by students’ critical thinking skill after theapplication of PBL model assisted by PhET to strengthen students’ critical thinking skill.Research and Development is a type of research used with 4D as the model and one grouppretest posttest design. Data collection in this research is by using validation, questionnaire,test, and observation while the technique of data analysis is using quantitative descriptiveanalysis. The instruments developed are lesson plans, student worksheets, critical thinkingskills tests and PhET simulation media for experiments. The final result in this result is to bringon a valid, practical and effective learning instrument in order to drill students’ critical thinkingskill on the subject of dynamic electricity